RANCANG BANGUN SISTEM PELAYANAN HOME SERVICE PADA YOYENA OPTIC BERBASIS WEB - yoga firstma heranda; Siti Nurmiati (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
This research is motivated by the condition of Indonesian people who are still averse to eye health. Optic as a provider of public health services has not been utilized optimally. Covid-19 pandemic in Indonesia causing the worse condition and impacting optic service providers. People are increasingly reluctant to check their eyes health, because it is difficult to get services from optic as a provider. The research titled: